Neuroscience on breaking bad news: Effects of physicians’ response on patient emotion and trust - Song, Yan; Xiu, Yifan; Li, Wei; Wang, Fang (Frontiers in Psychology, 2022)
Background: Delivering bad news has become one of the abilities that physicians need to improve. existing strategies lack systematic and structural responses to different cues and concerns of patients. Objective: This study aims to investigate whether and how the response styles of information delivery, empathy, and authority affect patient emotions and trust in order to present a structural response system. Furthermore, we explore the correlation between strategies and EEG markers to moderate emotions and trust. Methods: This research selects different scenarios and strategies in the context of breast cancer and performs two experiments. First, we performed a behavioral experiment with 93 medical students and 15 breast cancer patients. Moreover, an EEG experiment with 53 students via video stimuli was conducted to explore the moderate function between strategies and emotions/trust. We use time-frequency analysis and the repeated measure ANOVA method to explore the association between strategy and EEG components. Furthermore, we perform a GLM method to investigate the relationship between EEG components and patient emotion and trust. Results: For the first time, this study proposes the strategy matrix. The response strategies NPIm and NRIa play important roles in this system. In behavioral experiments, information delivery, empathy, and authority strategy significantly affect emotions and trust. The scenario is significant as a moderator. In the EEG experiment, strategy NPIm has more correlation with parietal alpha power than other strategies, and parietal alpha power has a significant effect on emotions, which verifies that empathy-related cerebral activities affect emotions and trust. Conclusions: According to the strategy matrix, physicians could apply strategy ERIa in most scenarios, and strategy NRIa in many scenarios, which means information provision is significant when it comes to responding to patients’ cues and concerns. The most important strategy that physicians need to avoid is the authority strategy. Refusing to respond to patients’ cues and concerns may cause their dislike. Moreover, through the EEG experiment, we verify that empathy affects emotions and trust from a neuroscience perspective and propose parietal alpha and frontal alpha as neuro-markers to moderate emotions and trust. Physicians could adjust strategies through these EEG markers.